Breast cancer and physical activity: A bibliometric analysis - Fresno-Alba, S.; Denche-Zamorano, Á.; Pastor-Cisneros, R.; Pereira-Payo, D.; Franco-García, J. M.; Jiménez-Castuera, R. (Frontiers in Oncology, 2023)
Breast cancer is a pathology suffered by millions of women worldwide, affecting the mental health, quality of life (QoL), physical functioning, cognitive functioning, and social and work life of surviving patients. Moreover, breast cancer is associated with weight gain, muscle atrophy, and weakness. Physical exercise appears to be an effective non-pharmacological treatment to improve short-term self-esteem, QoL, fatigue, and psychological factors such as depression, anxiety, happiness, and body image. The practice of physical activity is also associated with a reduction in the side effects of treatment. This bibliometric analysis analyzed the trend followed by publications on breast cancer and physical activity. The Web of Science database was used, and bibliometric laws were applied to identify the most prolific authors, the journals most involved in the field, and the countries, institutions, and keywords most used by the authors. Breast cancer and physical activity have an exponential trend in the number of publications, with Psycho-Oncology being the journal with the highest number of publications.